Academic production on strategies and/of innovation in Production Engineering (Revista Brasileira de Contabilidade e Gestão, 2023)
The work addresses the themes and innovation strategy with regard to scientific production, as part of works published in the database of Higher Education Personnel Improvement Coordination (CAPES) in the area of Production Engineering. Through issues related to the identification of the most productive authors, their home institutions, research environments where the studies were developed and journals where the papers were published it was possible to make a diagnosis (profile) and meeting the proposed objectives and they are related to the guiding questions. Periodicals for Qualis classification bases were consulted, and the cut-driven classification A1, A2, B1 and B2, the Production Engineering Department (Engineering III). Noteworthy is the absence of public organizations in the work, this fact may deserve further investigation of the reasons that make the public organizations are not subject to studies related to strategy, but especially related to innovation.
Keywords: innovation strategies; academic production; production engineering